Addition of the lewis acid Zn(C6 F5 )2 enables organic transistors with a maximum hole mobility in excess of 20 cm2 V-1 s-1 - Paterson,AF; Tsetseris,L; Li,R; Basu,A; Faber,H; Emwas,A-H; Panidi,J; Fei,Z; Niazi,MR; Anjum,DH; Heeney,M; Anthopoulos,TD (Advanced Materials, 2019)
Incorporating the molecular organic Lewis acid tris(pentafluorophenyl)borane [B(C6 F5 )3 ] into organic semiconductors has shown remarkable promise in recent years for controlling the operating characteristics and performance of various opto/electronic devices, including, light-emitting diodes, solar cells, and organic thin-film transistors (OTFTs). Despite the demonstrated potential, however, to date most of the work has been limited to B(C6 F5 )3 with the latter serving as the prototypical air-stable molecular Lewis acid system. Herein, the use of bis(pentafluorophenyl)zinc [Zn(C6 F5 )2 ] is reported as an alternative Lewis acid additive in high-hole-mobility OTFTs based on small-molecule:polymer blends comprising 2,7-dioctyl[1]benzothieno [3,2-b][1]benzothiophene and indacenodithiophene-benzothiadiazole. Systematic analysis of the materials and device characteristics supports the hypothesis that Zn(C6 F5 )2 acts simultaneously as a p-dopant and a microstructure modifier. It is proposed that it is the combination of these synergistic effects that leads to OTFTs with a maximum hole mobility value of 21.5 cm2 V-1 s-1 . The work not only highlights Zn(C6 F5 )2 as a promising new additive for next-generation optoelectronic devices, but also opens up new avenues in the search for high-mobility organic semiconductors.